Reformasi Birokrasi Dalam Pelayanan Publik di Kecamatan Tanimbar Selatan Kabupaten Kepulauan Tanimbar - Telly Muriany; Victor S. Ruhunlela (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2021)
Bureaucratic reform in public services in the south Tanimbar Island urgent. The facts show the South Tanimbar Islands is still faced various obstacles in public services, expecifically in the of education, health and licensing the District level as the spearhead of the South Tanimbar Islands (KKT) government in providing public services. This study used a qualitative because it fits with characteristics of the phenomenon researched verify reform issues that has been and can be done expected in accordance the character of the islands. The results showed in Tanimbar Selatan Subdistrict, (KKT) was not effective because of the problems faced related to the sub-district government's efforts to implement bureaucratic reform The authority given has not been fully implemented as expected. The aspect of organizational structure, it has implemented the principles arangged in the Government Regulation of the Republic of Indonesia Number 18 of 2016 about Regional Apparatus, it is expeted to prioritize aspects of interests and needs as well as the availability of Regional Government Budgets, the function of authority is often not adjusted to the capacity and comhpetence of the apparatus. it is based on likes and dislikes. technology-based information is still lacking, of course it has a negative impact on the low level of public services provided to the community, people are not satisfied believe in the public.